Adaptive Rule-Based Facial Expression Recognition - Ioannou, Spiros; Raouzaiou, Amaryllis; Karpouzis, Kostas; Pertselakis, Minas; Tsapatsoulis, Nicolas; Kollias, Stefanos D. (My University, 2004)
This paper addresses the problem of emotion recognition in faces through an intelligent neuro- fuzzy system, which is capable of analysing facial features extracted following the MPEG-4 standard and classifying facial images according to the underlying emotional states, following rules derived from expression profiles. Results are presented which illustrate the capability of the developed system to analyse and recognise facial expressions in man-machine interaction applications.
Keywords: Artificial intelligence--Congresses